2013
DOI: 10.1513/annalsats.201304-100oc
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Evaluating the Effect of Exacerbations on Physical Activity in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Physical activity decreased significantly during exacerbations. Reduction in activity occurs early during an exacerbation and persists for about 2 weeks after symptomatic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…Weight loss and wasting of muscle and bone tissue may be induced or accelerated during severe acute exacerbations requiring hospitalisation, due to convergence of different catabolic stimuli including malnutrition [58], physical inactivity [59], hypoxia, inflammation [60] and systemic glucocorticoids [61]. Moreover, this may be a time when energy intake may be compromised by practical difficulties in providing adequate nutrition due to breathlessness or other treatments such as noninvasive ventilation.…”
Section: Acute Exacerbationsmentioning
confidence: 99%
“…Weight loss and wasting of muscle and bone tissue may be induced or accelerated during severe acute exacerbations requiring hospitalisation, due to convergence of different catabolic stimuli including malnutrition [58], physical inactivity [59], hypoxia, inflammation [60] and systemic glucocorticoids [61]. Moreover, this may be a time when energy intake may be compromised by practical difficulties in providing adequate nutrition due to breathlessness or other treatments such as noninvasive ventilation.…”
Section: Acute Exacerbationsmentioning
confidence: 99%
“…This was somewhat unexpected, since in our analysis reporting directly measured physical activity outcome, clinically reported, and EXACT-only exacerbations had the same negative impact on physical activity, 6 and a recent study showed similar negative effects on health status. 23 Our study has several important limitations.…”
Section: Discussionmentioning
confidence: 59%
“…6 A review of wrist actigraphy suggests that this method is useful in the estimation of TST, sleep percentage, and wake after sleep onset; however, it is less consistent in the estimation of sleep latency. 16 …”
Section: Sleep Variablesmentioning
confidence: 99%
“…Indeed, lower physical activity levels are seen in COPD 133. Physical inactivity is associated with advanced disease stage,134, 135, 136 exacerbations,137, 138 and degree of emphysema 139. In addition, lung volume‐reduction surgery in patients with severe emphysema improved exercise performance due to reduced lung hyperinflation, less dyspnoea severity, and less cost of breathing 140.…”
Section: Putative Mechanisms Involved In a Disturbed Energy Balance Imentioning
confidence: 99%